Climate Change and Socio-Economic Impacts: Determinants of Vulnerability for Developing Countries - Dr. Afzaal Afzal; Dr. Nazia Salah ud Din; Dr. Sumera Tul Hasan (Journal of Peace, Development and Communication, 2024)
Climate change is the connected system of solar cycle that creates fluctuations weather arrays across tropics to polls. Anticipated climate changes for the 21st century have been encountered complex challenges for humanity that significantly influence over diverse components such as environmental, ecological, socio-political and socio-economic systems among others. This study incorporates a desk literature review and at the first step researchers shortlisted the keywords regarding climate change, socioeconomic impacts and determinants of vulnerability. Mixed method approach applied for this desk review. Numerous online search engines such as Google, Google Scholar, Scopus, Web of Science and Springer were selected to review the published research studies. The collected data comprises on various forms such as book chapters, books, research articles, reports, working papers, organizational evaluation studies and conferences papers. After strict inclusion and exclusion criteria researchers gathered to 89 studies from 31 publications outlets, which were interrelated to different search engine and covering climate change impacts on developing countries. The findings endorsed the climate change socio-economic impacts are more sever particularly in developing countries of south Asia like Pakistan. The astonishing and spatial heterogeneities are the clear indications for comprehensive integrated interventions, policies and procedure to eliminate or reduce socio-economic climate change impacts of developing countries.